Innovation in Post-Stroke Rehabilitation: Developing an Educational Application for Family Caregivers - 'Azzah, Taqiyyah Nurul; Pristianto, Arif (JISA(Jurnal Informatika dan Sains), 2025)
Stroke is a major cause of mortality and disability worldwide, with a rapidly increasing prevalence in Indonesia. Post-stroke patients often experience motor impairment, functional decline, and high dependency on family caregivers. Limited caregiver knowledge and skills often due to insufficient training, lack of access to reliable rehabilitation information, and minimal involvement in patient education during hospital discharge frequently hinder effective rehabilitation, reducing the quality of home care. This study aims to design and develop an audiovisual-based educational application to improve caregiver’s competence in assisting post-stroke rehabilitation. The application integrates structured video tutorials covering range of motion exercises, muscle strengthening, balance and coordination training, and daily transfer and ambulation guidance. The Research and Development (R&D) method was employed, as it enables systematic product development through iterative design, expert validation, and user testing to ensure the educational application is both affective and feasible for practical use. This approach is considered the most appropriate for developing and evaluating innovative educational media compared to purely observational or experimental methods. Expert judgment using the Content Validity Index (CVI) indicated high validity with an S-CVI/Ave score of 0.90, confirming the application’s feasibility as an educational medium. With a user-friendly interface and comprehensive multimedia content, the application provides practical knowledge accessible anytime and anywhere. The findings suggest that this innovation effectively supports caregiver education, enhances patient independence, and promotes better rehabilitation outcomes. Overall, the development of this application highlights the potential of digital health solutions in bridging gaps in post-stroke care and improving survivor’s quality of life.